NIKAH HAMIL DALAM PASAL 53 KHI: ANALISIS IMPLEMENTASI DAN PROBLEMATIKA MAQASHID ASY-SYARI’AH DI KECAMATAN KOTA AGUNG - Marwin; Agus Hermanto; Natika Audy (USRAH: Jurnal Hukum Keluarga Islam, 2026)
This study analyzes the application of Article 53 of the Compilation of Islamic Law (KHI) regarding the marriage of pregnant women as a result of adultery in the perspective of maqāṣid asy-syarī'ah, with a case study in Kota Agung District, Tanggamus Regency. The phenomenon of pregnancy outside of marriage not only presents moral issues, but also raises legal issues related to the protection of women, the certainty of the status of the child, and social approval. Article 53 KHI is presented as a legal solution by allowing marriage between a pregnant woman and the man who impregnated her without waiting for the child to be born. This study uses a descriptive qualitative approach through interviews, observations, and documentation studies, and is analyzed using source and method triangulation techniques. The results of the study show that the normative application of Article 53 of the KHI is in line with the objectives of maqāṣid of asy-syarī'ah, particularly in protecting women's honor (ḥifẓ al-'irḍ), lineage (ḥifẓ an-nasl), and safety of life (ḥifẓ an-nafs). This policy is considered capable of minimizing social stigma and providing administrative legal certainty for women and children. However, at the practical level, its implementation still faces moral and administrative challenges, as well as the risk of normalizing marriage during pregnancy if it is not accompanied by preventive training. Therefore, this study emphasizes the importance of repositioning maqāṣid asy-syarī'ah not only as the basis for legal permissibility, but also as an evaluative and preventive instrument in Islamic family law policy.